Evaluating of the Smart Mobility Concept through a Literature Review for the Development of Modern Urban Transportation System - afra, Liza; Emi Maulani; Khairul Amna; T Mudi Hafli; Aulia Rachman; Muhammad Azhari (Universitas Iskandar Muda, 2026)
This research conducts comprehensive evaluation of smart mobility concepts through literature review approach to develop sustainable modern urban transportation system development framework. Library research methodology was employed to analyze literature from various academic databases spanning 2020-2025, focusing on technological, social, economic, and environmental dimensions in smart mobility implementation. Research findings identify five principal components: multidimensional conceptual framework, integrated evaluation indicator systems, sophisticated technology integration architecture, multifaceted implementation challenges, and strategic best practices from successful global implementations. Results demonstrate that smart mobility success requires collaborative governance approaches, adaptive regulatory frameworks, and user-centric design principles considering local contexts and urban community needs. This research contributes to smart mobility knowledge base development and provides practical recommendations for stakeholders implementing effective and sustainable intelligent transportation systems within complex and dynamic modern urban contexts requiring sophisticated technological integration and comprehensive change management strategies.